TEKNIK DISKUSI BERBANTUAN APLIKASI ZOOM MEETING TERHADAP KETERAMPILAN SOSIAL SISWA KELAS XI SMK - Elita Mahpud; Wahyu Hidayat; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This research is motivated by students who have low social skills. The behavior shown by these students is difficult to interact with peers, unable to manage skills in dealing with stress, unable to understand other people's feelings, and from an academic point of view it will decline. Efforts were made to overcome these problems, namely by using a group guidance service strategy through discussion techniques carried out online through the zoom meeting application. The purpose of this study was to examine the effectiveness of group discussion techniques on social skills in students at the SMK (Vocational High School) level. This study uses an approach by collecting data in the form of questionnaires, observations, and interviews. The subjects in this study were six students and one BK teacher. The results of this study indicate that after the implementation of the discussion technique there were changes shown by the students. So it can be said that the implementation of the discussion technique in the group guidance strategy can be used on the social skills of class XI students at SMK Negeri 1 Cihampelas.Keywords: Discussion Techniques, Zoom Metting Applications, Social Skills